Lack of a relationship between vitamin D status and resting metabolic rate in Iranian adults. Issue 6 (4th December 2020) - Ebaditabar, Mojdeh; Babaei, Nadia; Davarzani, Samira; Imani, Hossein; Soares, Mario J.; Shab‐Bidar, Sakineh
Abstract: Objectives: Studies suggest a positive relationship between 25‐hydroxy vitamin D (25(OH)D)) and resting metabolic rate (RMR). We aimed to determine whether this relationship was also true of populations with very low vitamin D status. Methods: Fat mass (FM) and fat free mass (FFM) were determined from multifrequency bioimpedance analysis (InBody 720, Korea). RMR was based on indirect calorimetry (Cortex Metalyser 3B, Germany). Fasting blood measurements of 25(OH)D concentration, glucose and triglycerides were measured. Data were analyzed separately on men and women by tertile of vitamin D status and multiple linear regression analysis. Results: Two hundred and sixty‐three subjects (115 males; 148 females) with a mean age of 37 years and mean %body fat of 30.5% were studied. In women but not men, age, body weight, waist circumference, FM, and FFM increased significantly across tertiles of 25(OH)D. However, there was no difference in unadjusted or adjusted RMR across tertiles of 25OHD in both women and men. Stepwise forward regression analysis showed that age and FFM in men, age and FM in women but not by 25(OH)D, were determinants of RMR. In addition, RMR adjusted for age, sex, FM, FFM and triglyceride‐glucose index did not relate to 25(OH)D when linear ( r = 0, P = .98), quadratic ( r = 0.008, P = .34), or cubic ( r = 0.010, P = .43) relationships were tested. Conclusions: Residual variation in RMR did not relate to vitamin D status in a group of Iranian adults with very low vitamin D status. Future studies could examine whether such a relationship holds true, after the normalization of vitamin D status.